2023
DOI: 10.12688/wellcomeopenres.17261.2
|View full text |Cite
|
Sign up to set email alerts
|

Defective iron homeostasis and hematological abnormalities in Niemann-Pick disease type C1

Abstract: Background: Niemann-Pick disease type C1 (NPC1) is a neurodegenerative lysosomal storage disorder characterized by the accumulation of multiple lipids in the late endosome/lysosomal system and reduced acidic store calcium. The lysosomal system regulates key aspects of iron homeostasis, which prompted us to investigate whether there are hematological abnormalities and iron metabolism defects in NPC1. Methods: Iron-related hematological parameters, systemic and tissue metal ion and relevant hormonal and proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Many of these parameters had a similar direction of change between affected mice and human patients, with some in the latter group being at the low side of the normal range [93]. These findings indicated that Niemann-Pick type C1 disease causes dysregulation of iron homeostasis, including hematological alterations [93]. Consistent with these findings, a 2-year-old patient with Niemann-Pick type C had low blood iron with microcytosis [94].…”
Section: Disturbances To Iron Homeostasis In Niemann-pick Type C Diseasesupporting
confidence: 58%
See 2 more Smart Citations
“…Many of these parameters had a similar direction of change between affected mice and human patients, with some in the latter group being at the low side of the normal range [93]. These findings indicated that Niemann-Pick type C1 disease causes dysregulation of iron homeostasis, including hematological alterations [93]. Consistent with these findings, a 2-year-old patient with Niemann-Pick type C had low blood iron with microcytosis [94].…”
Section: Disturbances To Iron Homeostasis In Niemann-pick Type C Diseasesupporting
confidence: 58%
“…Alterations were observed across a variety of iron-related parameters in samples from both mice and humans with Niemann-Pick type C1 disease [93]. Examples of parameters that were affected include lower hematocrit, lower corpuscular hemoglobin and volume, lower levels of iron and light chain ferritin, and increased levels of soluble transferrin receptor in the serum of affected mice [93]. Many of these parameters had a similar direction of change between affected mice and human patients, with some in the latter group being at the low side of the normal range [93].…”
Section: Disturbances To Iron Homeostasis In Niemann-pick Type C Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…41 Previous studies have described an imbalance of iron metabolism and haematological abnormalities in NPC1 mouse models and in patients with Niemann-Pick disease type C1. 42 Further studies are required to understand the extent to which an inability to promote iron mobilization by autophagy and concomitant effects on mitochondrial function are linked with defects observed in patients. The platform we have described here and its application to relevant cell lineages linked with LSDs may facilitate identification of molecular defects or pathways with relevance to disease.…”
Section: Discussionmentioning
confidence: 99%
“…In general, dysregulated iron metabolism is associated with cognitive disorders, including memory and attention disorders, and anemia or, at least, an iron deficiency [ 36 , 37 ]. Ferritin levels in the cerebrospinal fluid are associated with inflammation markers, phospho-tau, and apolipoprotein E levels [ 38 ].…”
Section: Comorbidities Of Admentioning
confidence: 99%